TECTONOSTRATIGRAPHY OF RAKUBA SUB-BASIN, MUGLAD BASIN, SUDAN, NORTH AFRICA - ABDULLAH HANIF (NIM: 22014047), LUTFI
In the middle part of North Africa, there are 113 oil fields. 95 from Sudan (Muglad Basin and Melut) and 18 in Chad, which estimated 7.31 BBO, 13.42 TCF of natural gas, and 353 MB of natural gas liquids. The Muglad Basin is one of the great basins in North Africa. The basin is located in the southern of Sudanese state and South Sudan, covering 120,000 km2 area in both countries. The Muglad Basin consists of several sub-basins which already have an oil field inside. The Rakuba Sub-basin is one of many sub-basins in the Muglad Basin, which through the wildcat well, "Rabah-1", closed and abandoned as a dry well on April 16th, 2006. This tectonostratigraphic identification was conducted on the Rakuba Sub-basin in the El-Dain area with the coverage area of 1892 km2. Seismic analysis was conducted, including the observation of four two-dimensional seismic data controlled by "Rabah-1" wells. The method used in this research is a direct observation of geological and horizon structure patterns that recorded in seismic data by considering regional tectonic condition of research area, to explain tectonic setting using the analysis of structural depth map, thickness map, and palinspastic restoration method. Analysis of the well included a researched well data of "Rabah-1" which has wire line logging information, FMI, SWC, and biostratigraphy as the basis for research to identify structural and sedimentation patterns to determine the evolution or formation of Rakuba Sub-basin, and also as an information for determining the subsequent wells. The main tectonic periods in the Rakuba Sub-basin are: Pre-Rift Unit (Jurassic) and three units of Syn Rift-Sagging (Cretaceous - Recent) units. The Syn Rift-Sagging first cycle of Valanginian up to Albian or Lower Cretaceous, the second cycle of Santonian to Middle Paleocene, and the third cycle of Eocene to current time. The Rakuba Sub-basin evolved from the Jurassic until now consists of 34.62% of the bedrock (Jurassic) to the Top Kordofan Group (Recent) from the analysis of strain values. This basin beginning at the Jurassic period, characterized by L sediment. Abu Ghabra (Early Syn Rift) caused by the Central African Shear Zone that moves relatively dextral and produces transfer fault that generate the formation of the basin. The fault block with the relative direction of northeast-southwest stance continuously formed and rejuvenated from the Lower Cretaceous to the present day. By compensating for the extensional of the crust, a sagging phase initiated with thermal subsidence which characterized by massive sandstones (Bentiu Formation and Amal Formation). The abandonment of the "Rabah-1" wildcat well is due to the structural trap is heavily affected by tectonic activity such as normal fault rejuvenation, which couldnÃ‚Â’t function well as a good trap. Following the passive rift mechanism, geodynamic parameters and petroleum geology served as a reference for determining the location of new wells.